2019
DOI: 10.1177/0284185119864842
|View full text |Cite
|
Sign up to set email alerts
|

ADC quantification to classify patients candidate to receive bevacizumab treatment for recurrent glioblastoma

Abstract: Background Recurrent high-grade gliomas progressing after surgery and temozolomide plus radiation therapy have traditionally been treated using antiangiogenic drugs as the first-line therapy. Since the phase 3 EORTC 26101 trial showed no significant benefit of administering antiangiogenic drugs, the need to identify a biomarker to classify subgroups of potential responders has increased. Purpose To investigate the feasibility of using apparent diffusion coefficient as a predictor of the response of recurrent h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Moreover, the correlation threshold in this analysis suggests that these clinical variables offer complementary data to the radiomics, which may lead to the elaboration of other advanced models using different sources of data. Various studies have shown that the apparent diffusion coefficient (ADC) from diffusion MR could represent a good predictor of survival in GBM patients treated with bevacizumab [ 36 , 37 , 38 , 39 ]. In addition, perfusion-derived biomarkers were explored [ 40 , 41 , 42 ], but it should be mentioned that these methods depend largely on the type of the MRI machine, the sequence processing software, and the calculation algorithms and, therefore, are more difficult to apply to different centres in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the correlation threshold in this analysis suggests that these clinical variables offer complementary data to the radiomics, which may lead to the elaboration of other advanced models using different sources of data. Various studies have shown that the apparent diffusion coefficient (ADC) from diffusion MR could represent a good predictor of survival in GBM patients treated with bevacizumab [ 36 , 37 , 38 , 39 ]. In addition, perfusion-derived biomarkers were explored [ 40 , 41 , 42 ], but it should be mentioned that these methods depend largely on the type of the MRI machine, the sequence processing software, and the calculation algorithms and, therefore, are more difficult to apply to different centres in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%